Leaf-based energy harvesting and storage utilizing hygroscopic iron hydrogel for continuous power generation - Shuai Guo; Yaoxin Zhang; Zhen Yu; Ming Dai; Xuanchen Liu; Hongbo Wang; Siqi Liu; J. Justin Koh; Wanxin Sun; Yuanping Feng; Yuanzheng Chen; Lin Yang; et al. (Nature Communications)
Abstract In the era of big data, developing next-generation self-powered continuous energy harvesting systems is of great importance. Taking advantage of fallen leaves’ specific structural advantage gifted by nature, we propose a facile approach to convert fallen leaves into energy harvesters from ubiquitous moisture, based on surface treatments and asymmetric coating of hygroscopic iron hydrogels. Upon moisture absorption, a water gradient is established between areas with/without hydrogel coating, and maintained due to gel-like behaviors and leaf veins for water retention and diffusion restriction, thus forming electrical double layers over the leaf surface and showing capacitance-like behavior for energy charging and discharging. Besides, the specific leaf cell structures with small grooves enabled uniform carbon coatings instead of aggregations, and high electrical conductivity, resulting in 49 μA/cm2 and 497 μW/cm3 electrical output, achieving competitive performance with the state-of-art and potential for lower environmental impact compared to other types of energy harvesters.